SARS-CoV-2 Transmission by Arthropod Vectors: A Scoping Review. (8th August 2022) - Nekoei, Shahin; Khamesipour, Faham; Benchimol, Marlene; Bueno-Marí, Rubén; Ommi, Davood
Abstract : COVID-19 is a respiratory disease of worldwide importance as it has brought enormous health problems to the world's population. The best-known way of transmission of the virus is through aerosolization. However, research is needed to explore other transmission routes. Researchers hypothesized that arthropods could transmit SARs-CoV-2. This study is aimed at reviewing research on arthropods as possible reservoirs and/or vectors of SARS-CoV-2, the causative agent of COVID-19. Following PRISMA guidelines, we conducted a systematic review using several electronic databases/academic searches with the search terms "arthropods, " "coronavirus, " and "transmission." A total of 64 unique articles were identified, of which 58 were included in the review. The SARS-CoV-2 virus is tiny and invisible to the naked eye, and its presence in stools, droplets, and surfaces was detected. One doubt is whether insects can transmit the virus from one place to another. Thus, a healthy carrier of the COVID-19 virus can be at the root of the contamination of their community or their family through the transport of the virus by insects from the interior (flies, cockroaches, etc.) from their feces and food surfaces. Hygiene care within communities and families becomes a prime factor. Coronavirus infection is a significant public health problem around the world. The prevention and control of outbreaks remain very important, even with the production of new vaccines. The main option to achieve this is the proper management of the transmission of the virus. The registry of infected people is currently the basis for the transmission of COVID-19. However, questions about the possibility of infection from other sources and its prevention are not receiving adequate attention. Numerous studies have shown the possibility that SARS-COV-2 fragments could have a longer life than shed respiratory droplets. Also, this virus is larger than those of other coronavirus families.